MOTS-c Levels and Sarcopenia Risk in Chronic Peritoneal Dialysis Patients: A Pilot Study - Mariateresa Zicarelli; Marta Greco; Stefanos Roumeliotis; Maria Elisa Lo Vasco; Francesco Dragone; Christodoula Kourtidou; Ioannis Alekos; Roberta Misiti; Daniela Patrizia Foti; Giuseppe Coppolino; Vassilios Liakopoulos; Evangelia Dounousi; et al. (Medicina)
Background and Objectives: Sarcopenia is exceedingly frequent in end-stage kidney disease (ESKD) patients on dialysis, including those undergoing peritoneal dialysis (PD), and is of multifactorial origin. MOTS-c is a mitochondrial-derived peptide that promotes muscle growth whose levels are unbalanced in ESKD. In this study, we evaluated MOTS-c balance and its relationship with sarcopenia risk in an ESKD-PD cohort. Materials and Methods: MOTS-c was measured in serum, urine, and dialysate samples of 32 chronic PD patients. Patients were thus screened for sarcopenia risk by the SARC-F tool, anthropometric measurements, and physical performance tests. Results: PD patients with a very high sarcopenia risk (SARC-F ≥ 2) had significantly lower serum (sMOTS-c) and higher dialysate (dMOTS-c) levels, suggesting an increased peritoneal clearance of this substance (d/s MOTS-c). sMOTS-c levels were directly correlated with muscle performance in physical tests, while an opposite relationship was found with dMOTS-c and d/sMOTS-c. ROC analyses demonstrated the diagnostic potential of MOTS-c, particularly in combination with physical and anthropometric assessments, to identify PD patients at very high risk of sarcopenia. Conclusions: Chronic PD may negatively affect MOTS-c balance, which, in turn, may contribute to enhanced sarcopenia risk. Larger studies are needed to confirm these observations and to validate the potential utility of this substance as a biomarker for improving sarcopenia risk stratification in PD patients.